2016
DOI: 10.1155/2016/3961756
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Carries a Short-Term Rising Risk for Newly Diagnosed Diabetes Mellitus Independently of Weight Gain: A 6-Year Retrospective Cohort Study

Abstract: Background. The effects of smoking on human metabolism are complex. Although smoking increases risk for diabetes mellitus, smoking cessation was also reported to be associated with weight gain and incident diabetes mellitus. We therefore conducted this study to clarify the association between smoking status and newly diagnosed diabetes mellitus. Methods. An analysis was done using the data of a mass health examination performed annually in an industrial park from 2007 to 2013. The association between smoking s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…The risk of incident diabetes (RR = 1.36) in ex-smokers who had quit for less than 5 years declined gradually to RR 1.23 in those who had stopped smoking between 5 and 9 years and declined to an almost equal risk of a non-smoker of RR 1.02 for those abstinent for over 10 years (RR = 1.02). In a retrospective study conducted on 8452 male T2DM patients in Taiwan [33], the RR was was 1.50 for smokers compared to non-smokers. Smoking abstinence contributed to increasing the risk for T2DM in the first year after quitting smoking (RR = 1.83) and in the second year (RR = 2.02), declining rapidly thereafter.…”
Section: Does Quitting Smoking Decrease the Incidence Of Diabetes?mentioning
confidence: 99%
“…The risk of incident diabetes (RR = 1.36) in ex-smokers who had quit for less than 5 years declined gradually to RR 1.23 in those who had stopped smoking between 5 and 9 years and declined to an almost equal risk of a non-smoker of RR 1.02 for those abstinent for over 10 years (RR = 1.02). In a retrospective study conducted on 8452 male T2DM patients in Taiwan [33], the RR was was 1.50 for smokers compared to non-smokers. Smoking abstinence contributed to increasing the risk for T2DM in the first year after quitting smoking (RR = 1.83) and in the second year (RR = 2.02), declining rapidly thereafter.…”
Section: Does Quitting Smoking Decrease the Incidence Of Diabetes?mentioning
confidence: 99%
“…5 Additionally, smoking cessation generally decreases vascular risk for newly diagnosed diabetes mellitus. 96…”
Section: Smoking and Diabetes Complicationsmentioning
confidence: 99%
“…7 Cigarette smoking is independently associated with the incidence of T2DM. 24 Although the mechanisms involved are not clear yet. Smoking is associated with insulin resistance, inflammation and dyslipidaemia.…”
Section: Discussion Summary Of Resultsmentioning
confidence: 99%
“…A 14-year prospective cohort study in South Korea showed that the risk of DM among men and women who smoked 20 or more cigarettes a day was 1.55 times higher than that in non-smokers 7. Cigarette smoking is independently associated with the incidence of T2DM 24. Although the mechanisms involved are not clear yet.…”
Section: Discussionmentioning
confidence: 99%